Vaccine Designs Utilizing Invariant NKT-Licensed Antigen-Presenting Cells Provide NKT or T Cell Help for B Cell Responses - Fujii, Shin-ichiro; Yamasaki, Satoru; Sato, Yusuke; Shimizu, Kanako (Frontiers in Immunology, 2018)
Vaccines against a variety of infectious diseases have been developed and tested. Although there have been some notable successes, most are less than optimal or have failed outright. There has been discussion about whether either B cells or dendritic cells (DCs) could be useful for the development of antimicrobial vaccines with the production of high titers of antibodies. Invariant (i)NKT cells have direct antimicrobial effects as well as adjuvant activity, and iNKT-stimulated antigen presenting cells (APCs) can determine the form of the ensuing humoral and cellular immune responses. In fact, upon activation by ligand, iNKT cells can stimulate both B cells and DCs as via either cognate or non-cognate help. iNKT-licensed DCs generate antigen-specific follicular helper CD4+T cells, which in turn stimulate B cells, thus leading to long term antigen-specific antibody production. Follicular helper iNKT cell-licensed B cells generally produce rapid, but short term antibody. However, under some conditions in the presence of Th cells, the antibody production can be prolonged. With regard to humoral immunity, the quality and quantity of Ab produced depends on the APC type and the form of the vaccine. In terms of cellular immunity and, in particular, the induction of cytotoxic CD8+T cells, iNKT-licensed DCs show prominent activity. In this review we discuss differences in iNKT-stimulated APC types and the quality of the ensuing immune response, and also discuss their application in vaccine models to develop successful preventive immunotherapy against infectious diseases.